2014
DOI: 10.1038/nutd.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, gut microbiota and faecal short chain fatty acids are linked in adult humans

Abstract: Background/Objectives:High dietary fibre intakes may protect against obesity by influencing colonic fermentation and the colonic microbiota. Though, recent studies suggest that increased colonic fermentation contributes to adiposity. Diet influences the composition of the gut microbiota. Previous research has not evaluated dietary intakes, body mass index (BMI), faecal microbiota and short chain fatty acid (SCFA) in the same cohort. Our objectives were to compare dietary intakes, faecal SCFA concentrations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
357
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(398 citation statements)
references
References 43 publications
(57 reference statements)
23
357
4
4
Order By: Relevance
“…9,10,20 However, several studies in adults have found an increase of Bacteroidetes, 21,22 less proportion of Firmicutes, unaltered Bacteroidetes ratio, 23 or no differences in the proportions between these two phyla with the obesity degree. 24,25 In the present study, we found a high relation of Firmicutes/Bacteroidetes in obese children which is consistent with other studies. 7,[26][27][28] These controversial results could be explained by lifestyles, ethnic groups, 29,30 geographic origin 23 and even by the different experimental, bioinformatics and cohort selection methodologies used.…”
Section: Discussionsupporting
confidence: 82%
“…9,10,20 However, several studies in adults have found an increase of Bacteroidetes, 21,22 less proportion of Firmicutes, unaltered Bacteroidetes ratio, 23 or no differences in the proportions between these two phyla with the obesity degree. 24,25 In the present study, we found a high relation of Firmicutes/Bacteroidetes in obese children which is consistent with other studies. 7,[26][27][28] These controversial results could be explained by lifestyles, ethnic groups, 29,30 geographic origin 23 and even by the different experimental, bioinformatics and cohort selection methodologies used.…”
Section: Discussionsupporting
confidence: 82%
“…Although some studies did not find a difference in F:B ratio [73], or even found an inverse F:B ratio [74], they did find significantly more SCFAs in obese subjects compared with lean subjects [73,74]. Fernandes et al [73] also found that the amount of fecal SCFAs did positively correlate to the F:B ratio and found an inverse association between Bacteroidetes and body mass index (BMI). Moreover, a progressive increase in Bacteroidetes was associated with voluntary weight loss in a dietary intervention study following 12 obese subjects over the course of a year [5].…”
Section: Microbial Characteristics In Obesitymentioning
confidence: 82%
“…Furthermore, an increase in the Firmicutes:Bacteroidetes (F:B) ratio has been associated with obesity in mice [32,72] and humans [25,71]. Although some studies did not find a difference in F:B ratio [73], or even found an inverse F:B ratio [74], they did find significantly more SCFAs in obese subjects compared with lean subjects [73,74]. Fernandes et al [73] also found that the amount of fecal SCFAs did positively correlate to the F:B ratio and found an inverse association between Bacteroidetes and body mass index (BMI).…”
Section: Microbial Characteristics In Obesitymentioning
confidence: 99%
“…129 −131 After absorption, SCFAs are processed in the liver for use in gluconeogenesis and lipogenesis. 132 −135 Interestingly, dietary supplementation with SCFAs has been shown in rodents to promote a switch from lipid synthesis to oxidation and to protect against obesity and insulin resistance. 38 , 39 Bacteria from the family Enterobacteriaceae , particularly Escherichia coli , have been associated with increased systemic lipopolysaccharides 136 , increased risk of obesity, inflammation, reduced glomerular filtration rate, increased serum cystatin C and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%